1995
DOI: 10.1021/j100033a012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Homogeneous Nucleation in Supercooled Clusters of tert-Butyl Chloride. Transition from Tetragonal to Monoclinic Phase

Abstract: In a series of molecular dynamics runs on 188-molecule clusters of rert-butyl chloride spontaneous transitions from the orientationally disordered tetragonal phase to the ordered monoclinic phase occurred during cooling. Nucleation rates exceeding critical nuclei m-3 s-l were determined at 100, 90, and 80 K. These were found to be consistent with a rate 8 orders of magnitude lower measured at 156 K in experiments with much larger clusters, when compared on the basis of the classical theory of nucleation. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…It is worth commenting that the curves in Figure 11 display irregularities, some more than others, in the vicinity of the transition from bcc to monoclinic. In some prior simulations 11 it had been observed that the greater compactness of the packing in the low-temperature phase created a tension in the phase surrounding it that tended to disrupt the outer structure. This course of events may help to account for the irregularities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth commenting that the curves in Figure 11 display irregularities, some more than others, in the vicinity of the transition from bcc to monoclinic. In some prior simulations 11 it had been observed that the greater compactness of the packing in the low-temperature phase created a tension in the phase surrounding it that tended to disrupt the outer structure. This course of events may help to account for the irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] If a realistic intermolecular interaction function can be constructed, it is possible to follow the molecular trajectories that lead to nucleation. Indeed, many MD investigations of phaselike changes in extremely small clusters of atoms have already been made, 12 and several have been carried out on clusters of polyatomic molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of desktop workstations that are faster than yesterday's supercomputers, it is now feasible to examine details of nucleation that have previously been obscure. The systems studied in most previous simulations of nucleation in condensed phases have been freezing atomic liquids, although a few studies of polyatomic systems undergoing freezing or solid-state transitions in small clusters at deep supercooling have been reported. The present investigation follows up several of these.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of solid state and freezing transitions have been observed in large molecular clusters as they cool in supersonic flow . Several of these transitions have also been seen to occur spontaneously in molecular dynamics (MD) simulations of cooling clusters. Clusters are particularly convenient systems for MD simulations of phase transitions because clusters avoid the severe limitations imposed by periodic boundary conditions. In both the experimental and computational research it is possible to determine rates of genuinely homogeneous nucleation, a notoriously difficult phenomenon to achieve, verify, and characterize by more conventional techniques.…”
Section: Introductionmentioning
confidence: 99%